Azerbaijan’s Balancing Act in the Ukraine Crisis - Valiyev, Anar (PONARS Eurasia, 2014)
The crisis in Ukraine that began with the Euromaidan movement and flight of President Viktor Yanukovych put the Azerbaijani government in an uncomfortable position. For the last few years, Baku has been building good relations with Russia, hoping to persuade Moscow to stand on Azerbaijan’s side in resolving the Karabakh conflict. Massive arms purchases from Russia, a benevolent foreign policy toward Moscow, and Baku’s unwillingness to deepen relations with the European Union and NATO have all created a reasonably positive image of the country in the eyes of Russian authorities. The Russian occupation of Crimea and support for separatists in the Donbas have complicated Azerbaijan’s position, however. While the Azerbaijani government fully supports Ukraine, Baku cannot afford to spoil relations with Moscow due to the latter’s significant leverage in the Caucasus. Azerbaijan is left with the option of trying not to irritate Russia while staying on the side of those who object to Russia’s intervention. At the same time, the Ukraine crisis and a fear of interrupted gas supplies has led to renewed attention by the European Union to the need for an alternative transport system for delivery of gas from the Caspian region to European states. European consumers have even begun to express interest in revitalizing the idea of a Transcaspian gas pipeline that would deliver Turkmen gas to Europe via Azerbaijan. Overall, the Ukraine crisis has made Baku’s geopolitical stance a high prize.
PONARS Eurasia Policy Memo
Keywords: Azerbaijan -- Politics and government -- 1991- -- Congresses.; Ukraine -- Politics and government -- 1991- -- Congresses.; Russia (Federation) -- Politics and government -- 1991- -- Congresses.; Azerbaijan -- Foreign relations -- Congresses.; Ukraine -- Foreign relations -- Congresses.; Russia (Federation) -- Foreign relations -- Congresses.